CLOSING LECTURE AT THE XVI INTERNATIONAL CONGRESS OF BIEN, SEOUL, SOUTH KOREA, JULY 7-9, 2016 - Suplicy, Eduardo Matarazzo (Práticas de Administração Pública, 2017)
Lecture to The International Seminar on the Basic Income or the Universal Citizen’s Income  organized by the Mexican Senate and  CEPAL, April 19-20, 2016 Contribution to the book “Integral Policy towards the First Infancy” about the São Paulo Carinhosa Program and Brazil Carinhoso Program (São Paulo and Brazil Caressing Programs), of the Municipality of São Paulo Program of Mayor Fernando Haddad, June 2016.